The Antecedents of Clearance Sales Store Satisfaction - Hemalatha, M.; Sridevi, P. (Journal of Contemporary Research in Management (JCRM), 2013)
Retail items that are â€œclearedâ€ at the end of its season are referred to as seasonal merchandise. When merchandise is cleared, it is often sold below cost, at a price that will be called the residual value. Retail promotions or special sales events are designed to increase store traffic and sales and, ultimately, store profits. In general, these clearance sales are appropriate for those industries that face customers whose willingness to pay for the product diminishes over the selling season. In recent yearsÂ  more and more retail products have been sold on sale and at higher percentage markdowns. Pricing practices began to change in the late sixties as more products, particularly apparel products were sold at markdown. The increase in the seasonal variation of apparel prices over time is related to the growing importance of fashion. The uncertainty theory predicts the probability that a shirt is sold on sale, and the percentage markdown should be higher at the end of the season than atÂ  the beginning of the season. This study seeks to examine the influence of store attributes on clearance sales store satisfaction. A total of 664Â  shoppers were surveyed during clearance sales in three different IndianÂ  cities and we have constructed a model to study the clearance sales storeÂ  attributes on store satisfaction. The clearance sales store satisfaction model discussed in this study can be used by retailers to develop a moreÂ  effective clearance sales strategy.